MODEL PEMBERDAYAAN EKONOMI MASYARAKAT PESISIR PANTAI MELALUI PENGEMBANGAN DESA WISATA BUDAYA BERBASIS KULINER BAHAN BAKU LOKAL PADA PANTAI WISATA PULAU KABUPATEN ALOR - Zainudin Adang Djaha; Herni Sunarya (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2020)
One of the priority programs of the Alor district government is alleviating poverty in coastal communities with a strategy to develop culinary tourism on the island of Kepa in Alor Kecil. The island has a stretch of white sand as soft as flour and clear blue sea far from the crowds. Looking at the sea in Alor from the coast of Kepa Island, the tranquility feels reassuring. The clear sea is protected inrows of sturdy hills on the surrounding islands. Small waves run slowly along fishing boats that occasionally pass. Kepa Island is a very good place for swimming, snorkeling and diving. This priority program has not been carried out maximally for the people on Kepa Island and its surroundings,namely community empowerment through culinary tourism. During this time the island of Kepa tourism was only made as a recreation area and an area for fishing for the community. The purpose of this study is to identify cultural culinary potential based on local raw materials that can improve thecommunity economy on Kepa Island and develop a Coastal Community Empowerment Model to improve the economy of coastal communities based on Local Raw Materials. The method of data analysis used in this research is descriptive research method. with data analysis techniques namelySWOT analysis, Internal Factors Analysis Summary (IFAS) analysis, External Factors Analysis Summary (Efas), Analytical Hierarchy Process (AHP) method, exploring the perceptions and expectations of tourists and society, as a basis for modeling and further testing. Based on an in-depth analysis of exploring culinary culture based on local raw materials, the researchers then made a model that was in accordance with the wishes and expectations of coastal communities. The design of the Coastal Community Economic Empowerment model covers four fields including economics, environment, infrastructure and accessibility.